2013
DOI: 10.35536/ljb.2013.v2.i1.a4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Training on Employees’ Performance in Commercial Banks in Urban Lahore

Abstract: Training helps meet specific skill deficits in employees' performance. Successful organizations and managers realize the importance of human resources; trained human resources are key to maintaining a competitive advantage in today's constantly changing global environment. An efficiently implemented training program leads to better employee performance. This study aims to test for important training-related variables that significantly affect the performance of bank employees in urban Lahore. Using earlier stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Productivity of employees is directly tied to performance of banks. A similar study by Tahir & Sajjad (2013) on commercial banks in Lahore indicated that training significantly influenced bank performance.…”
Section: Empirical Reviewmentioning
confidence: 75%
“…Productivity of employees is directly tied to performance of banks. A similar study by Tahir & Sajjad (2013) on commercial banks in Lahore indicated that training significantly influenced bank performance.…”
Section: Empirical Reviewmentioning
confidence: 75%
“…And their findings showed that that proper needs assessment, effectiveness of training programme, investment in training, and provision of training all significantly affect employees' job performance [20].…”
Section: Literature Reviewmentioning
confidence: 99%